Humanism in No Hana and Tsumi Shi No Hi By Abe Tomoji (Orientalism Study) - Irvina Restu Handayani (Jurnal Penelitian Humaniora, 2018)
This study was aimed at describing humanism in Shi no Hana and Tsumi no Hi by Abe Tomoji. This research was a literature research that used qualitative descriptive method. The data were in the form of text excerpts, both words, phrases and sentences containing humanism. The data were sourced from Shi no Hana novels and Tsumi no Hi by Abe Tomoji published by Shinbungeisha. The data collection techniques used was library research techniques. The collected data was then analyzed based on orientalism theory. To gain the valid result, a triangulation test was carried out, namely time triangulation. The result shows that Hinobe as an invader still maintains human nature, self-concept and freedom. The nature of human beings as individual beings is a feature of humanism in Shi no Hana and Tsumi no Hi. Despite being an invader, Hinobe realized his differences with other Japanese people regarding the ideals of peace. Freedom in Shi no Hana and Tsumi no Hi is divided into physical and psychological freedom, both of which are only Hinobe consciousness not realization. The self concept is divided into physical, attitude and intelligence.Humanisme dalam Shi No Hana dan Tsumi No Hi Karya Abe Tomoji (Kajian Orientalisme)Penelitian ini bertujuan untuk mendeskripsikan humanisme dalam Shi no Hana dan Tsumi no Hi karya Abe Tomoji. Penelitian ini merupakan penelitian sastra yang menggunakan metode deskrptif kualitatif. Data berupa kutipan teks, baik kata, frasa maupun kalimat yang mengandung humanisme. Data diperoleh dari sumber data berupa novel Shi no Hana dan Tsumi no Hi karya Abe Tomoji yang diterbitkan oleh Shinbungeisha. Teknik pengumpulan data menggunakan teknik penelitian pustaka. Data yang sudah terkumpul kemudian dianalisis dengan mendasarkan pada teori orientalisme. Untuk mendapatkan hasil yang benar-benar valid, dilakukan uji triangulasi, yaitu triangulasi waktu. Berdasarkan hasil penelitian diketahui bahwa Hinobe sebagai penjajah masih mempertahankan hakikat manusia, konsep diri dan kebebasan. Hakikat manusia sebagai makhluk individu menjadi keistimewaan humanisme dalam Shi no Hana dan Tsumi no Hi. Meskipun sebagai penjajah, Hinobe menyadari akan perbedaan dirinya dengan orang Jepang lain terkait cita-cita perdamaian. Kebebasan di dalam Shi no Hana dan Tsumi no Hi terbagi atas kebebasan fisik dan psikologis, yang keduanya hanya berupa kesadaran Hinobe bukan realisasi. Konsep diri terbagi menjadi penilaian fisik, sikap dan kecerdasan.